Throughput planning of Port Klang's timber terminal. - Munisamy @ Doraisamy, Susila; Mohd, Ismail (1990)
In this paper we describe a system called SM1 for throughput planning of the timber terminal at Port Klang,Malaysia. The SM1 devised for the timber terminal analyses the interaction of terminal equipments (forklifts,tractors,trailers and shipcranes for ship loading) to describe the performance of each of the equipments and the throughput of the terminal.